Penyertaan Mahram Pada Pelaksanaan Haji Dan Umrah - Atiyatul Ulya; Maulana Maulana (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2016)
Umrah carried out by agencies of a travel agency with several provisions issued by the ministry of religion RI. The meaning of mahram that was set by the ministry of religion is include to a mahram pilgrims, mahram referred in family relationship or marriage. This is regulated by the rules of registration of pilgrims and associated with the administration of Hajj and Umrah service. So that they try as much as possible to include a mahram as defined in the shari'ah by including the documents to indicate the mahram validation. They try to make it all based on the documents which corroborate these requirement as evidence of the validity of requirement. The provision as above, would be very detrimental to women those will carry out the pilgrimage, because they will be burdened with additional costs while they did not get the expected benefits. For contextual understanding that participation of mahram can be interpreted as safety. But in pilgrimage, mahram has not been found detailed provisions in the pilgrims discurs. By paying a